Cardiac amyloidosis: A case report - Ruiz-Mori, Enrique (2018)
Cardiac amyloidosis is a rare clinical entity and, therefore, almost unknown. It shows as a restrictive cardiomyopathy, since it is an infiltrative disease caused by the extracellular deposition of amyloids in the cardiac wall. Although it may be systemic, the heart condition determines its poor prognosis. This is the case of a 38-year-old patient who was admitted for dyspnea and severe fatigue. He was diagnosed with IgA multiple myeloma, lambda light chains, clinical stage IIIB, and initiated treatment with cyclophosphamide, thalidomide and dexamethasone. The patient stopped the treatment, and returned after one year and 2 months with an advanced disease and presence of amyloidosis. The patient progressed torpidly and eventually died. A review of the medical literature is performed concerning amyloidosis types, physiopathology, diagnostic methods and treatment.